Peptide glutamine supplementation for tolerance of intermittent exercise in soccer players - Favano, Alessandra (2008)
OBJECTIVE: To investigate whether supplementation of carbohydrate together with peptide glutamine would increase exercise tolerance in soccer players. METHODS: Nine male soccer players (mean age: 18.4 ± 1.1 years; body mass: 69.2 ± 4.6 kg; height: 175.5 ± 7.3 cm; and maximum oxygen consumption of 57.7 ± 4.8 ml.kg-1.min-1) were evaluated. All of them underwent a cardiopulmonary exercise test and followed a protocol that simulated the movements of a soccer game in order to evaluate their tolerance to intermittent exercise. By means of a draw, either carbohydrate with peptide glutamine (CARBOGLUT: 50g of maltodextrin + 3.5g of peptide glutamine in 250 ml of water) or carbohydrate alone (CARBO: 50g of maltodextrin in 250 ml of water) was administered in order to investigate the enhancement of the soccer players' performances. The solution was given thirty minutes before beginning the test, which was performed twice with a one-week interval between tests. RESULTS: A great improvement in the time and distance covered was observed when the athletes consumed the CARBOGLUT mixture. Total distance covered was 12750 ± 4037m when using CARBO, and 15571 ± 4184m when using CARBOGLUT (p<0.01); total duration of tolerance was 73 ± 23 min when using CARBO and 88 ± 24 min when using CARBOGLUT (p<0.01). CONCLUSION: The CARBOGLUT mixture was more efficient in increasing the distance covered and the length of time for which intermittent exercise was tolerated. CARBOGLUT also reduced feelings of fatigue in the players compared with the use of the CARBO mixture alone.